Numerical simulations and optimization of solar air heaters. (5th November 2020) - Korpale, V.S.; Deshmukh, S.P.; Mathpati, C.S.; Dalvi, V.H.
Highlights: The empirical correlations are developed to obtain Nu number and friction factor. The designs of rectangular section finned surfaces are optimized. Maximum THP of 2.77 is obtained at optimum values of input parameters. The optimal size of rectangular section fin has been calculated. Abstract: Different surface modification techniques have been used for enhancement of heat transfer from absorber plates of solar air heaters. It is necessary to have accurate values of design parameters within the operational window while designing the heat transfer equipments. The present work is focused on the development of empirical correlations and evaluation of maximum thermohydraulic performance of a rectangular section ribs installed in solar air heaters considering all the design combinations within the given range of input parameters. It is prescribed by design of experiment algorithms particularly with response surface methodology considering four input parameters viz., Reynolds number ranging from 4000 to 20000, relative rib pitch ranging from 5 to 60, relative rib height ranging from 0.065 to 0.252 and relative rib width ranging from 0.5 to 10. The maximum THP obtained is 2.77 at Reynolds number 20000, relative rib pitch 17.22, relative rib height 0.044 and relative rib height 0.5. The optimal values of design parameters have been verified with CFD simulations and experiments. The errors are within acceptable limit proving the accuracy of empirical correlations used for the design of solar artificial air heater and proper selection of model equations.